Problematic issues of applying the category of “guilt” to legal entities - Yu. M. Zhornokui (Bulletin of Kharkiv National University of Internal Affairs)
An analysis of the Ukrainian legislation, as well as doctrinal approaches to understanding the guilt of a legal entity as a participant in civil relations, was carried out. It was concluded that the issue of the possibility of guilt in a legal entity within the limits of civil liability is determined by several factors of both an objective and subjective nature, namely: a) various mechanisms of forming the will of participants in civil legal relations; b) lack of understanding of the manifestation of the legal entity's own guilt as an independent participant in civil relations, or the guilt of members of its bodies, participants or employees; c) the absence of a direct indication in the current Civil Code of Ukraine on the existence of guilt in a legal entity, since the code (Article 96) contains a norm only about its responsibility.